Bioremediation of Heavy Metal Contaminated Wastewater Using Indigenous Bacteria and Fungi - Miftah Alfeetouri Miftah (African Journal of Advanced Pure and Applied Sciences, 2025)
This study examines the use of native microbial strains to remove heavy metals from polluted wastewater. We isolated a Cd-tolerant Ochrobactrum intermedium (strain BB12) from sewage and a Cladosporium fungal isolate (NRCA8) from industrial effluent, based on colony morphology and molecular identification (16S rRNA, ITS). Laboratory experiments evaluated metal tolerance and biosorption. Ochrobactrum BB12 grew in up to 150 mg/L Cd (MIC) and reduced Cd in solution by biosorption as seen in SEM/EDX and FTIR analyses. Cladosporium NRCA8 removed >90% Pb²⁺ at pH 5.5. Batch tests varied pH, contact time, biomass dose, and initial metal concentration to determine removal efficiency and adsorption capacity (q). Data were fitted to Langmuir and Freundlich isotherms and pseudo-first/second-order kinetics. For example, an archaeal biomass achieved 83.4% Cd removal at pH 8 and a qₘₐₓ ≈128 mg/g. SEM/EDX and FTIR showed metal binding on cell walls, and immobilized biomass columns exhibited stable removal (modeled by Thomas/Yoon-Nelson equations). Fungal treatments often outperformed bacteria; e.g., Aspergillus and Trichoderma bioleached 8× more As from marine sediment than bacteria. Statistical analysis (ANOVA, R²) validated model fits. Finally, treated effluent showed reduced toxicity, demonstrating risk mitigation. These results highlight the potential of indigenous microbial consortia in heavy metal bioremediation, offering a low-cost, sustainable approach compared to conventional methods.